Analisis manajemen krisis Zara Fashion di Masa Pandemi Covid-19 - Sanika Sembiring; Harbet, Parlin (Jurnal Public Relations (J-PR), 2020)
Since the WHO (World Healthy Organization) announced that COVID-19 is a global pandemic, consumer behavior in various business sectors has changed. Consumers are becoming very careful about consuming and trying to take care of themselves and their families to survive in this situation. Even areas of the city and state began to close. There is no traffic and normal activities like a few months ago. No wonder the health crisis has an impact on the economic crisis simultaneously. This also affects the company Zara. Reported from the news portal CBCN. This research method uses a descriptive qualitative approach with news content analysis methods in several online media. Currently, the company Zara is also focusing on a short-term program, namely by producing masks for medical workers and patients to help fight the corona virus. This global pandemic has impacted several fashion industries, businesses have had to close half of their stores. And also make updates in the trading system. Because sales have decreased by 4.9 percent.